The first cut-off points for generalized and abdominal obesity in predicting lipid disorders in a nationally representative population in the Middle East: The National Survey of Risk Factors for Non-Communicable Diseases of Iran - Delavari, Alireza; Kelishadi, Roya; Forouzanfar, Mohammad H.; Safaei, Afshin; Birjandi, Fariba; Alikhani, Siamak (Archives of Medical Science, 2009)
Introduction: To determine the prevalence of dyslipidaemia and the optimal cut-off points of body mass index (BMI) and waist circumference (WC) at which abnormal lipid levels can be identified with maximum sensitivity and specificity in a nationwide population-based sample for the first time in the Middle East. Material and methods: Using a probability proportional to size, multistage cluster sampling method, a sociodemographically representative sample of 3024 of the Iranian population aged 25-64 years living in urban and rural areas of all 30 provinces of the country was studied. Results: The mean age of participants was 41.3 (0.07) years. The receiver operating curve (ROC) analysis showed that the optimal cut-off value of BMI to identify with maximum sensitivity and specificity the detection of lipid disorders was 25 kg/m 2 for males and 26-28 kg/m 2 for females. Considering WC, among males this optimal cut-off value was 88-89 cm for high total cholesterol (T. Chol), low HDL-C and high triglycerides (TG), whereas it was lower (86 cm) for predicting high LDL-C. Among females, this cut-off value was 83-84 cm for predicting high T. Chol, high LDL-C and high TG, but it was higher (90 cm) for low HDL-C. The most prevalent type of abnormal lipid level was low HDL-C. Conclusions: The optimal cut-off points provided in the current study might serve as a public health action threshold in the Middle East population. The very high prevalence of high TG and low HDL-C suggest that current guidelines for screening lipid disorders that are based on total and LDL cholesterol should consider such ethnic differences.